1987
DOI: 10.1021/ie00062a008
|View full text |Cite
|
Sign up to set email alerts
|

Gum and deposit formation from jet turbine and diesel fuels at 100.degree.C

Abstract: Rates of oxidation and gum formation for six hydrocarbons, three jet turbine fuels and three diesel fuels have been measured at 100 °C in the presence of f-Bu202 as initiator. Four of the six fuels oxidize faster at 100 °C than in previous work at 130 °C without initiator. For any single substrate, the amount of gum produced for the oxygen absorbed is similar at 100 and 130 °C, even with large changes in rates and t-Bu202 concentrations. Thus, one mechanism of gum formation is intimately associated with oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…The important factor here is that the rate of step 4, Scheme , increases by the square of the peroxyl radical concentration while the rate of step 5 only increase linearly. Consistent with our hypothesis are literature examples of several fuels in which the rate of oxidative deposit formation actually decreases when the fuel stress temperature is increased from 100 to 130 °C (i.e., so-called self-retarding fuels ) …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The important factor here is that the rate of step 4, Scheme , increases by the square of the peroxyl radical concentration while the rate of step 5 only increase linearly. Consistent with our hypothesis are literature examples of several fuels in which the rate of oxidative deposit formation actually decreases when the fuel stress temperature is increased from 100 to 130 °C (i.e., so-called self-retarding fuels ) …”
Section: Resultssupporting
confidence: 87%
“…Previous workers have also noted similar temperature deposit correlations under a variety of experimental conditions. 4,[13][14][15] Since the flowing reactor temperatures used in these experiments are known to cause complete dissolved oxygen consumption, 3 equivalent amounts of oxygen are consumed in these experi-ments. It should also be noted that in the PSU flowing reactor experiments the fuel passes through a filter after exiting the heating element and cooling.…”
Section: Each Flowing Reactor Experiments Inmentioning
confidence: 99%
“…In a number of industrial processes, uncontrolled polymerization of olefins is known to be a potential source of operation problems, including equipment fouling and, in most severe cases, unit shutdown. For example, parasite polymerization occurs in fuel tanks at room temperature because of a slow oxidation mechanism , that yields soluble gums and heavier oxygenated polymers that can deposit on the walls . In spark-ignited gas engines, olefin-containing fuels lead to the formation of polymer by gum deposition inside fuel nozzles under the high pressure and temperature conditions of injection .…”
Section: Introductionmentioning
confidence: 99%
“…For example, parasite polymerization occurs in fuel tanks at room temperature because of a slow oxidation mechanism , that yields soluble gums and heavier oxygenated polymers that can deposit on the walls . In spark-ignited gas engines, olefin-containing fuels lead to the formation of polymer by gum deposition inside fuel nozzles under the high pressure and temperature conditions of injection . The effect is enhanced in the presence of fuel impurities, such as compounds containing nitrogen or sulfur heteroatoms. , In petrochemistry, olefin production equipment (including compressors, separators, condensers, or distillation columns) may face similar issues and experience serious production losses…”
Section: Introductionmentioning
confidence: 99%
“…0888-5885/90/ 2629-0324802.50/0 drocarbon mixtures (Mayo and Lan, 1983). Walters et al (1949) studied the gum formation in cracked gasoline and found that the gum and peroxide formation is autocatalytic in nature.…”
mentioning
confidence: 99%